Surfactant flushing remediation of o-dichlorobenzene and p-dichlorobenzene contaminated soil. (October 2017) - Pei, Guangpeng; Zhu, Yuen; Cai, Xiatong; Shi, Weiyu; Li, Hua
Abstract: Surfactant-enhanced remediation is used to treat dichlorobenzene (DCB) contaminated soil. In this study, soil column experiments were conducted to investigate the removal efficiencies of o-dichlorobenzene ( o -DCB) and p-dichlorobenzene ( p -DCB) from contaminated soil using micellar solutions of biosurfactants (saponin, alkyl polyglycoside) compare to a chemically synthetic surfactant (Tween 80). Leachate was collected and analyzed for o -DCB and p -DCB content. In addition, soil was analyzed to explore the effect of surfactants on soil enzyme activities. Results showed that the removal efficiency of o -DCB and p -DCB was highest for saponin followed by alkyl polyglycoside and Tween 80. The maximum o -DCB and p -DCB removal efficiencies of 76.34% and 80.43%, respectively, were achieved with 4 g L −1 saponin solution. However, an opposite result was observed in the cumulative mass of o -DCB and p -DCB in leachate. The cumulative extent of o -DCB and p -DCB removal by the biosurfactants saponin and alkyl polyglycoside was lower than that of the chemically synthetic surfactant Tween 80 in leachate. Soil was also analyzed to explore the effect of surfactants on soil enzyme activities. The results indicated that surfactants were potentially effective in facilitating soil enzyme activities. Thus, it was confirmed that the biosurfactants saponin and alkyl polyglycoside could be used for remediation of o -DCB and p -DCB contaminated soil. Graphical abstract: Highlights: Enhanced soil flushing of o, p -DCB by biosurfactants saponin and alkyl polyglycoside was studied. The removal efficiency of biosurfactants and chemically synthetic surfactant for o, p -DCB in soil was compared. Surfactants were potentially effective in facilitating soil enzyme activity.